THE INSURGENT ARCHITECTS’ RIGHT TO THE CITY IN THE BRAZILIAN AMAZON - Schor, Tatiana (Ra’e Ga: o Espaço Geográfico em Análise, 2015)
The Right to the City is not only a theoretical concept but also a political ideal. This paper will present empirical research and theoretical aspects ofo this right, and possibilities of change, through an analysis of a group of cities in the Brazilian Amazon, those located along the rivers Solimões and Amazonas, Amazonas state, Brazil. Cities have an in si and a per si character. Considering the in si character a city can be studied and comprehended in itself, its morphological structures (physical, imaginary) and its fluxes (of things, people and power). This understanding is a necessary first movement for change and how this understanding is done, the methodological procedures, will limit or expand transformative possibilities. The revolutionary force of the Right to the City is to comprehend the city per si, as entity that can influence and take lead on the changes that transform the premises of the future. Areas with low city density, as the Amazon, a city itself has an important (use)value. The functions that are intrinsic to cities are available in definite places/locations. These cities are special places, still opened to change, for the handcuffs of private property of land as defined by capitalism are not fully established. Land property in most of the cities in the western section of the Brazilian Amazon is not defined by law: houses and gardens merge. The socioecological relationships that define this diverse socio-biodiversity may give interesting insights to the discussion of the Right to the City world-wide.